Conversion of units of length from the Czech state standard to the geodetic baseline Javoriv - Jiří Lechner; Nikolai Sergeevich Kosarev; Igor Sergeevich Trevoho (Acta Polytechnica, 2022)
Modern society cannot do without high quality geospatial data. This need constantly strengthens with the growth of the information society and the emerging cyber society. Validity and quality of geospatial data is strongly connected to the level of its metrological service. It is necessary to conduct National metrological comparisons, in order to maintain an effective measuring infrastructure both inside a single country and in the whole Europe. The main result of such a comparison is a validation of actual values of key parameters of state standards. The article presents results of a conversion of unit of length of the state standard of the Czech Republic to the geodetic baseline Javoriv (Ukraine), as performed by the staff of the Research Institute of Geodesy, Topography and Cartography (RIGTC). The conversion was realised in cooperation with Lviv Polytechnic National University (Ukraine). High-precision measuring equipment used during the conversion includes: the Leica AT401 laser tracker and the Leica Nova MS50 electronic total station. A comparison of the measured length sections of the geodetic baseline Javoriv, performed by VUGTK employees, with the measurement results performed on a geodetic baseline Javoriv by specialists of the National Science Center (NSC) Institute of Metrology, gave a very good consistency. This is a sign of high quality results of comparative international measurement. It is planned to continue with the common efforts in the field of comparative international measurements between the Czech Republic and Ukraine in order to determine the actual values of the length sections of the geodetic baseline Javoriv.